2014
DOI: 10.1021/nn505688b
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled Nanotubes Formed by Catanionic Mixtures of Drug Amphiphiles

Abstract: Mixing of oppositely charged amphiphilic molecules (catanionic mixing) offers an attractive strategy to produce morphologies different from those formed by individual molecules. We report here on the use of catanionic mixing of anticancer drug amphiphiles to construct multiwalled nanotubes containing a fixed and high drug loading. We found that the molecular mixing ratio, the solvent composition, the overall drug concentrations, as well as the molecular design of the studied amphiphiles are all important exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 70 publications
3
59
0
Order By: Relevance
“…High hydrophilic content always tends to afford filamentous structures, while lower hydrophilic content prefers rod-like or spherical structures. 45, 56, 57 As a result, uniform nanorods were obtained at higher HCPT to Ce6 ratios through the confinement of the core HPCT nanostructure with an energy minimization process. It has been reported that cylindrical nanostructures exhibit very good pharmacokinetics and efficiency in drug delivery even better than spherical ones because of their multiple endocytotic mechanisms, enhanced internalization rates and effective adhesion to cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…High hydrophilic content always tends to afford filamentous structures, while lower hydrophilic content prefers rod-like or spherical structures. 45, 56, 57 As a result, uniform nanorods were obtained at higher HCPT to Ce6 ratios through the confinement of the core HPCT nanostructure with an energy minimization process. It has been reported that cylindrical nanostructures exhibit very good pharmacokinetics and efficiency in drug delivery even better than spherical ones because of their multiple endocytotic mechanisms, enhanced internalization rates and effective adhesion to cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…195 By mixing of oppositely charged CPT drug amphiphiles (catanionic mixing), the Cui Lab reported on the formation of multiwalled nanotubes containing a fixed and high drug loading. 196 They found that the molecular mixing ratio, the solvent composition, the overall drug concentrations, as well as the molecular design are all important experimental parameters contributing to the tubular morphology.…”
Section: Small Molecule Sapdsmentioning
confidence: 99%
“…It was postulated that the initial short filaments were the kinetic product of the hydrophobic collapse, with further rearrangement of the internal structure allowing the formation of β-sheet hydrogen bonds to give twisted two-filament fibrils as the thermodynamic product. A second approach was demonstrated by the catanionic mixing of oppositely charged derivatives of Cui’s four-CPT bearing drug amphiphile, qCPT-Sup35-K 2 and qCPT-Sup35-E 2 [110], which led to the formation of large, multi-walled nanotubes (Fig. 6C); very distinct structures from the smaller nanotubes formed by the individual components.…”
Section: Supramolecular Nanostructures Formed By Amphiphilic Prodrugsmentioning
confidence: 99%
“…(C) Cryogenic TEM image of a catanionic mixture of two oppositely charged drug amphiphiles, showing the formation of form large multiwalled nanotubes. Adapted from ref [110], copyright 2014 Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%